Management of conflict injuries to the upper limb. Part 2: reconstruction and managing complications. (September 2022) - Roberts, Darren C.; Jose, Rajive M.; Duraku, Liron S.; Wordsworth, Matthew; Foster, Mark; Mortiboy, Deborah; Sellon, Edward; Stapley, Sarah A.; Power, Dominic M.
This is the second of a two-part review article on the management of conflict injuries, focused on the reconstructive strategies for bone, nerve and soft tissue and to provide guidance on assessing and managing common complications associated with complex upper limb injuries. Following assessment and early surgical management, the conflict casualty will require further wound evaluation and planning prior to definitive reconstruction of limb injuries. Surgical management of the upper limb injury should aim, where possible, to preserve the limb and allow functional reconstruction. The principles of the second look procedure are to assess wound progression, further reduce the risk of infection and plan definitive reconstruction with adequate soft tissue cover. The prerequisites for successful surgical reconstruction are a stable patient, combined orthoplastic surgery expertise supported by physiotherapists and hand therapists.